The Effect of Promotion and Customer Satisfaction on the Loyalty of E-Wallet Dana Users in Samarinda - Sukirman, Sukirman; Zilfana, Zilfana; Sonaria, Mita; Sitorus, Astrid Napita; Themba, Orfyanny S; Yulindawati, Yulindawati (Sebatik, 2024)
The E-Wallet DANA service represents a breakthrough in leveraging current technological advancements to facilitate transactions across various digital products. It is designed with maximum security and user comfort, aiming to provide seamless convenience through its diverse service features. This study aims to examine the impact of promotion and user satisfaction on the loyalty of E-Wallet DANA users in Samarinda. A quantitative research method was employed, with 109 respondents selected as the sample using a Likert scale. The results of the multiple linear regression analysis revealed that promotion had no significant effect on user loyalty, while consumer satisfaction positively influenced the loyalty of E-Wallet DANA users.